Навчальний додаток для пошуку коренів многочленів на комплексній площині - Мічурін, І. Є. (ХНУРЕ, 2021)
The need to find the roots of polynomials arises in many problems: school exercises, calculations in higher mathematics, physics, chemistry, industry, and so on. One of the fastest methods for finding roots is Newton's method. The question of choosing the initial approximation is not obvious. What root we get, depends on what initial approximation we choose. The purpose of the created computer application is to help students and researchers of technical fields to investigate the problem of finding the roots of a polynomial (real and complex) by the iterative method of Newton.
Науковий керівник – к.т.н., доц. каф. ПІ Груздо І.В.
Keywords: додаток для пошуку; корень многочленів